METODE PEMBELAJARAN AL-QUR’AN DALAM MENGINTERNALISASIKAN NILAI-NILAI AHKLAK QUR'ANI DI MA NURUL HASAN BRANI WETAN TAHUN AJARAN 2017-2018 - Soleha, Siti Amilus; Samsudin, Samsudin (LP3M UNZAH GENGGONG, 2019)
ABSTRACT One aspect of religious education that is lacking attention is the education of reading the Qur'an. In general, parents are more focused on general education so that many Muslim children who can not read and write the Qur'an. As a first step is to lay a strong religious foundation on children in preparation for wading their lives and future lives. As where the word